1990
DOI: 10.1346/ccmn.1990.0380311
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations in Chlorite and Illite in a Diagenetic Sequence from the Imperial Valley, California

Abstract: Abstract--Samples of cuttings from the Borehard A-2 well, Imperial Valley, California, were collected over a measured borehole temperature interval 135* to 275*(2. The < 0.5-/~m (e.s.d.) fraction was separated using high-gradient magnetic separation (HGMS) to create a nonmagnetic fraction rich in illite and a magnetic fraction rich in chlorite. Chlorite was less easily separated from illite in lower temperature samples (< 200"C), presumably due to the presence of polymineralic grains of chlorite and illite. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Such a sequence has been only rarely described in pelitic rocks (Frey 1978;Weaver et al 1984;Robinson and Bevins 1986), for which chlorite commonly has been inferred to form as a byproduct of the smectite-to-illite reaction or from alteration of kaolinite or berthierine (Hower et al 1976;Boles and Franks 1979;Ahn and Peacor 1985;Walker and Thompson 1990). Dioctahedral phyllosilicates such as illite or muscovite are usually present in amounts much greater than those of trioctahedral minerals in shales, commonly reflecting the presence of either dioctahedral smectite as an original detrital phase as in Gulf Coast sediments, or volcanic ash that was subsequently altered to form dioctahedral smectite.…”
Section: Relation Between the Abundance Of Trioctahedral Phyllosilicamentioning
confidence: 99%
“…Such a sequence has been only rarely described in pelitic rocks (Frey 1978;Weaver et al 1984;Robinson and Bevins 1986), for which chlorite commonly has been inferred to form as a byproduct of the smectite-to-illite reaction or from alteration of kaolinite or berthierine (Hower et al 1976;Boles and Franks 1979;Ahn and Peacor 1985;Walker and Thompson 1990). Dioctahedral phyllosilicates such as illite or muscovite are usually present in amounts much greater than those of trioctahedral minerals in shales, commonly reflecting the presence of either dioctahedral smectite as an original detrital phase as in Gulf Coast sediments, or volcanic ash that was subsequently altered to form dioctahedral smectite.…”
Section: Relation Between the Abundance Of Trioctahedral Phyllosilicamentioning
confidence: 99%
“…Berthierine has been inferred to occur as a metastable prograde precursor to chlorite in rocks undergoing diagenesis (Velde et al, 1974;Iijima and Matsumoto, 1982;Jahren and Aagaard, 1989;Walker and Thompson, 1990). A small increase in diagenetic grade (or burial depth) results in replacement of berthierine by chlorite.…”
Section: Alteration Of Chlorite To Berthierinementioning
confidence: 99%
“…Powder X-ray diffraction and chemical analytical data have led to the identification of berthierine in only a small number of shallow marine sediments and unmetamorphosed clastic sedimentary rocks (Velde et al, 1974;Frey, 1970Frey, , 1978Iijima and Matsumoto, 1982;Curtis et al, 1985;Taylor, 1990;Walker and Thompson, 1990). However, transmission electron microscopic (TEM) observations of clastic sediments have shown that berthierine typically is admixed with diagenetic chlorite at very fine scales (e.g., Lee and Peacor, 1983;Ahn and Peacor, 1985;Amouric et al, 1988;Jahren and Aagaard, 1989;Jiang et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations